Dialektyka neutralności - Momro, Jakub (Śląskie Studia Polonistyczne, 2013)
The author makes an attempt to work out a model of reading works by Krzysztof Siwczyk, one of the most interesting poets last years. On the one hand, the author of Koncentrat seems to be immersed in radical modernist discourses (e.g. numerous references to Maurice Blanchot’s writing) and, on the other, Siwczyk writes in the world right after “closing” and fulfilling all possible modern narrations. According to the author of the article, the poet proposes a special vision of poetry as discourse and metatheory, and unique, as well as consciously introduced rhetoric of writing as catastrophe of sense, representation, thought and image on the map of the Polish poetry. All these elements create a rich and complex dialectics of neutrality in which a post-historical time is tightly related to the experience of a momentary taking over the world by language.